Diabetes and Reactive Balance: Quantifying Stepping Thresholds With a Simple Spring Scale to Measure Fall-Risk in Ambulatory Older Adults. (November 2021) - Rosenblatt, Noah J.; Young, Jennifer; Andersen, Ryley; Wu., Stephanie C.; Crews, Ryan T.
Background: Fall-risk assessments for patients with diabetes fail to consider reactive responses to balance loss. The purpose of this study was to assess the feasibility of using a simple clinical tool to evaluate the impact of diabetes and fall history on reactive balance in older adults. Methods: We recruited 72 older adults with and without diabetes. Postural perturbations were applied by a waist-mounted spring scale. Stepping thresholds (STs) in the anterior and posterior directions were defined as the lowest spring-loads that induced a step. Balance was assessed via the National Institutes of Health Toolbox Standing Balance Test, and lower extremity sensation was assessed using vibratory perception threshold and Semmes-Weinstein monofilaments. Fall history over the past year was self-reported. Cox regressions and analysis of variance were used to compare hazard rates for stepping and observed STs between groups. Results: Anterior STs were elicited in 42 subjects and posterior STs in 65 subjects. Hazard rates for posterior ST were significantly affected by diabetes, with greater hazards for fallers with diabetes versus control fallers and nonfallers, after accounting for balance and sensory loss. For those who stepped, ST was lower in the posterior direction for the diabetes group. Additionally, anterior but not posterior ST was lower in all fallers vs all nonfallers. Conclusions: The waist-mounted spring scale is a clinically implementable device that can assess ST in older adults with diabetes. Using the device, we demonstrated that ST was affected by diabetes and could potentially serve as a fall-risk factor independent of balance or sensory loss.